The Socio-Communicative Development of Preterm Infants Is Resistant to the Negative Effects of Parity on Maternal Responsiveness - Caldas, Ivete F. R.; Garotti, Marilice F.; Shiramizu, Victor K. M.; Pereira, Antonio (Frontiers in Psychology, 2018)
Humans are born completely dependent on adult care for survival. To get the necessary support, newborns rely on socio-communicative abilities which have both innate and learned components. Maternal responsiveness (MR), a critical aspect of mother-infant interaction, is a robust predictor of the acquisition of socio-communicative abilities. However, maternal responsiveness (MR) is influenced by parity, since the mother relies on a limited capacity of cognitive control for efficient attachment with the offspring. This fact is of particular concern for preterms, whose developing brain already faces many challenges due to the premature emergence from the womb’s controlled environment and may be negatively affected by the number of siblings on the quality of attachment to its mother. Thus, in the present work, we aimed to verify how parity interferes with MR and whether it affects the development of socio-communicative abilities of preterm infants. We used the Social Interaction Rating Scale (SIRS) and the mother-child observation protocol in 18 dyads with gestational age < 36 weeks. Dyads were separated into three groups: primiparous with twin pregnancy (TPM), primiparous (PM), and multiparous (MP). Dyadic behavior was evaluated at 3, 6, 9, and 12 months. Our results show that offspring size affects MR, but not the socio-communicative development of preterm infants during the first year, suggesting a level of resilience of brain systems supporting the attachment to caregivers